MATA KULIAH BERORIENTASI DUNIA KERJA PADA KURIKULUM JURUSAN SASTRA JEPANG DI INDONESIA - Idrus Idrus; Fithyani Anwar (Universitas Andalas, 2018)
In this study, we discussed work field oriented course on Japanese Department’s curriculum in Indonesia. The method used is qualitative method with research data are curriculums’ used on several Japanese Departments in Indonesia such as Japanese Department of Universitas Andalas, Universitas Indonesia, Universitas Padjadjaran, Universitas Gajah Mada, Universitas Brawijaya, Universitas Hasanuddin, Universitas Udayana. The purpose of this research was to discuss and explain the course in some Japanese Department that could be applied directly in the work field. Work field oriented course on Japanese Department were described and then analyzed the relevance and benefits for the students in the work field. The results showed that there were similarities in work field oriented course in some Japanese Departments although the name/label of the course was slightly different. This proves all Japanese Departments had same mission to produce graduates who was not only master in Japanese language but also had other skills that could be used actively wherever they are. Key words: work field, course, curriculum, Japanese Department, Indonesia